Wave propagation study for axi-symmetric 2D problems of a generalized thermo-visco-elastic half space. Issue 7 (3rd July 2019) - Sherief, H. H.; Hamza, F. A.; Abd El-Latief, A. M.
Abstract: We consider axi-symmetric 2D problems for a visco-elastic half space. We utilize Laplace and Hankel transforms. Asymptotic expansions are used to study wave propagation in the medium. The temperature, displacement, and stress distributions are computed and represented graphically for a specific problem.